PERANCANGAN SISTEME-VOTINGUNTUK PEMILIHAN KETUA BEM (BADAN EKSEKUTIF MAHASISWA) DI STKIP PGRI SUMATERA BARAT - Wando, Hari; Pratama, Ade; Samudra, Ami Anggraini (Jurnal EDik Informatika, 2019)
The election of the Student Executive Board (PilkaBEM) is an inseparable part of the STKIP PGRI Campus Agenda in West Sumatra as a democratic campus. PilkaBEM still uses conventional voting, which uses paper media to vote on PilkaBEM. In implementing the conventional pilkaBEM voting system, it has many weaknesses.Current advances in information technology have brought huge changes to people, including ways to conduct voting. The use of computer technology in the conduct of voting is known as electronic voting or commonly referred to as e-voting. The research method used in this research is system development, which is an experiment to design e-voting applications using the PHP programming language, HTML tags and to use the MySQL database as a database server. E-votingapplications are developed using web-based.The e-voting application is in accordance with the AD / ART PilkaBEM and is in accordance with the PilkaBEM principle applicable at the STKIP PGRI West Sumatra campus. The e-voting application is built using the PHP programming language, and utilizes the MySQL database as a database server. Development of a more attractive appearance without reducing user convenience.